(untitled) (Research, Society and Development, 2022)
Objective: To describe the most relevant findings in the literature on the treatment of breast cancer in times of the COVID-19 pandemic. Methodology: It is an integrative review on the way in which breast cancer treatment was being provided in the pandemic period, carried out between October and November 2021, in the following databases: Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), PEDRo, Scopus (Elsevier Science), Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed) e Scientific Eletronic Library Online (SciELO). Results: 19 publications were analyzed that discussed ways of monitoring breast cancer patients during the pandemic, their limitations and impacts caused. The main results found point to the use of tele-services, an increase in the number of cancellations of exams and consultations, in addition to a drop in the practice of physical activity and the emergence of emotions that can generate psychological pathologies in the COVID-19 scenario. Closing remarks: The studies found reveal the fragility of health systems and the lack of public health policies aimed at women undergoing breast cancer treatment, in times of public health emergencies. This fact negatively impacts the quality of life and prognosis of these patients.